Composi????o corporal, perfil lip??dico e marcadores de estresse oxidativo em atletas master de diferentes modalidades - Aguiar, Samuel da Silva (2017)
The effect of physical exercise throughout life on body composition, lipid profile and oxidative stress is not clearly explained. Thus, the objective of this study was to investigate and compare body composition, lipid profile and oxidative stress in master athletes of different modalities, healthy young and sedentary adults. Seventy healthy men were divided into five groups: young non-athletes (n = 17; 22.7 ?? 7.0 years), adult non-athletes (n = 12; 45.5 ?? 9.9 years), long distance master athletes (n = 18; 53.0 ?? 8.2 years), speed master athletes (n = 13; 50.0 ?? 8.9 years) and fighters (n = 10; 46.1 ?? 7.0 years). The body composition was evaluated through skin folds and perimetry. Blood samples were taken at rest for analysis of lipid peroxidation (TBARS), superoxide dismutase activity, uric acid and clinical parameters (lipid profile and fasting glycemia) by spectrophotometry. Young nonathletes and master runners had significantly lower percentage of fat and higher lean mass compared to adult non-athletes and fighters (p < 0.05). In addition, the lipid profile and lipid peroxidation did not differ significantly in the studied groups. The groups of young nonathletes and long-distance master runners showed higher superoxide dismutase activity than the other groups (p < 0.05), whereas adults non-athletes presented higher concentration (p < 0.05) of acid uric compared to all other groups. The data suggest that healthy young and master runners present better body composition and lipid profile compared to sedentary middle-aged individuals and master fighters. In addition, healthy youngsters and longdistance runners present greater antioxidant defense than the other groups, may be reflect on the improvement of quality of life during the aging process.